Phytochemicals and potential health effects of Sambucus williamsii Hance (Jiegumu). Issue 1 (December 2016) - Xiao, Hui-Hui; Zhang, Yan; Cooper, Raymond; Yao, Xin-Sheng; Wong, Man-Sau
Abstract Sambucus williamsii Hance (Jiegumu ) is traditionally used in Chinese medicine to treat bone and joint diseases. The major phytochemicals inS. williamsii are lignans, terpenoids, and phenolic acids, together with trace amounts of essential oils, minerals, amino acids, and natural pigments. In this review, a database search for studies published from 1990 to November 2015 was conducted using PubMed, the China Academic Journals Full-Text Database, and Google Scholar with the keywords "Sambucus williamsii Hance", "Sambucus williamsii ", "Sambucus williamsii  + clinic", "Sambucus williamsii  + biology", "Sambucus williamsii  + chemicals", and "Jiegumu ", which covered chemical studies, cell culture studies, animal experiments, and clinical studies. This article reviewed the compounds isolated fromS. williamsii that may reduce the risk of cancer, and exert antifungal, antioxidant, anti-inflammatory, bone fracture healing, and antiosteoporotic effects.